The Influence of Psychological Approaches in Divorce Mediation in Religious Courts - Arman Nugraha; Citra Dewi (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2021)
This research examines the influence of a psychological approach in divorce mediation in religious courts in Indonesia, with a focus on how this approach can overcome the factors that cause mediation failure. Through qualitative methods, data was collected from in-depth interviews with mediators who have extensive experience in divorce mediation and have undergone psychology training. The research results show that mediators with psychological training are more effective in managing the emotional dynamics of mediation, reducing resistance, and facilitating constructive communication between the parties involved. This research also highlights the importance of integrating psychological skills in mediator training to increase mediation success. Recommendations are aimed at developing mediator training curricula and policy adjustments that support more empathetic and effective mediation practices in religious courts.